PENGARUH LEMAK TERHADAP KUALITAS ECLAIRS - Akhyar, Febriyana; Syarif, Wirnelis; Holinesti, Rahmi (Journal of Home Economics and Tourism, 2017)
This research was based on the absence of some fat used in making eclairs. The used of fat commonly applied in the manufactured of eclairs is margarine. The purpose of the research to analyzed the effect of fat used on the quality of eclairs that includes volume, shape, color, aroma, texture and taste. The type of research was purely experimental with Rancangan Acak Lengkap Method. Research variables included independent variable that was X0 (margarine), X1 (butter), X2 (cooking oil), X3 (white butter). The dependent variable was the quality of eclairs. The data used were Primery Data source from 30 semi trained panelist by proposing the organoleptic test format. Analysis of data with ANAVA if Fcount>Ftable the proceed with Duncan Test. The result of research was that there were real difference to the quality of eclairs with different fat usage including volume, texture and taste because Fcount>Ftable. On the quality of shape, color and aroma. There was no real difference because Fcount<Ftable.Keyword : Eclairs, Quality, Margarine, Butter, Cooking Oil, White Butter.